Processos de inclusão/exclusão escolar: análise do impacto da prova brasil na escolarização do público alvo da educação especial - Witeze, Erika Marinho (2016)
This work discusses the issues related to the participation of the target audience of special education in Prova Brasil, covering two state schools in the city of Goiânia-GO. It adopts the historical-critical pedagogy and the cultural-historical theory as its theoretical frameworks. We investigate the conditions of these students participation in Prova Brasil, considering the special features arising from the deficiencies, global development disorders and high skills/giftedness and also knowing that they are enrolled in regular rooms. In addition, it makes explicit the articulations between the policies of inclusion and large-scale evaluation, revealing the developments of the neotechnicist proposal in the field of special education. Finally, it seeks to identify the proposals and/or alternatives suggested by teachers and managers regarding to the demands brought by Basic Education Evaluation System (SAEB) in Brazil. Based on the legal frameworks and academic production on inclusive education and largescale assessments, we talk about the consequences of regulating and monitoring the quality of education. We also show how the increased visibility of the Basic Education Development Index (IDEB) and the vertical control of the results intensifies the competition between schools, justifying mechanisms such as accountability, meritocracy and privatization of public education. Moreover, from a documentary and bibliographic research, participant observation of school routines and semi-structured interviews with managers, support staff and specialized teachers, we underline the tensions and contradictions experienced by the establishments investigated in reconciling two different models of evaluation and organization of pedagogical work: the first, based on the recognition of diversity and on the flexibilization of curricular contents, didactic resources and temporality; the second, founded on the homogenization of students performance on standardized tests, in a classificatory and market perspective. Finally, we evidence the coexistence between processes of inclusion/exclusion as a result from the use of Prova Brasil for measuring the students performance in specific areas of the curriculum. Considering the neoliberal context, we question the limits of the speech defending differences and its power to confront the various forms of exclusion and marginalization of students with disabilities and other special needs. In this perspective, we point out the possible contributions of Participatory Institutional Assessment (PIA) – as an anti-regulatory strategy – on developping socially referenced quality standards, which may provide support for the educational work in inclusive schools.